Neonatal intestinal obstruction : patterns, problems and outcome (Bangladesh Medical Journal Khulna, 2013)
Neonatal intestinal obstruction is the most common surgical emergency in newborn. Ideally neonatal surgery should be done in an organized neonatal surgical unit. This study was done mostly in general surgical setup in Khulna without any facility of NICU and TPN. The aim of this study was to detect the patterns of neonatal intestinal obstruction and to find out the problems and outcome of surgical treatment. This retrospective study was done between January 2008 and December 2010, in Khulna Medical College Hospital, Khulna Shishu Hospital and a private clinic in Khulna. A total of 205 neonates with intestinal obstruction were treated surgically. Babies of both sexes up to 28 days of age were included in this study. Common causes of neonatal intestinal obstruction were anorectal malformation (ARM), intestinal atresia, Hirschsprung's disease (HD), meconium ileus and malrotation of midgut. Male-female ratio was 1.6:1 and about 13% was premature. Out of 205 neonates, there were ARM-73, HD-47, meconium ileus-38, intestinal atresia-29, malrotation-13 and others-5. Total 172 (84%) survived. Those were ARM (94%), Hirschsprung's disease (91%), meconium ileus (79%), intestinal atresia (55%), malrotation of gut (85%) and others (40%). Overall mortality after initial surgical treatment was 16%. Prognosis of surgical treatment depends on early intervention, expert anaesthesia, associated anomaly and complication, gentle handling of delicate tissue and intensive postoperative management. Medical practitioners were the first attending physician in most instances. So both physicians and surgeons have a contributing role in reducing mortality. DOI: http://dx.doi.org/10.3329/bmjk.v45i1-2.13638 Bang Med J (Khulna) 2012; 45 : 6-10